Crucial Role of CD4+CD 25+ FOXP3+ T Regulatory Cell, Interferon-γ and Interleukin-16 in Malignant and Tuberculous Pleural Effusions. (February 2013) - Ibrahim, Lamiaa; Salah, Manal; Rahman, Azema Abd El; Zeidan, Amany; Ragb, Maha
<x xml:space="preserve">Abstract</x> The differential diagnosis between malignant and tuberculous exudative pleural effusions is an important clinical problem. The aim of current study is to evaluate the frequencies of T-regulatory cells (Treg) on the basis of distinct phenotypes in the differential diagnosis between malignant and tuberculous pleural effusion. In addition, to evaluate Interferon-gamma (IFN- γ) and interleukin-16 (IL-16) levels and their correlation to Treg cells in malignant and tuberculous pleural effusions. Sixty patients with pleural effusion (26 tuberculous and 34 malignant) and 20 healthy controls were included in the study. Pleural fluid and peripheral blood were assessed for frequencies of T regs, IL-16, and IFN-γ. Pleural effusions from both tuberculous and malignant groups represented significantly higher levels (more in TB) for the following cell populations than peripheral blood: total lymphocytes, CD3+lymphocyte, CD4+CD25+lymphocyte and Treg (CD4+ CD25+FoxP3+). Levels of IL-16 and IFN-γ in tuberculous group were significantly higher than that in malignant group. Regulatory T cells, INF-γ and IL-16 are new important tools for differentiation between tuberculous and malignant pleural effusion.